Implementation of Flash Cards as Visual Media in Akidah Akhlak Learning for Grade II Students at Cahaya Cendekia Excellent Elementary School - Nadiyatus Sholihah; Ainur Rofiq Sofa (Lembaga Penerbitan, Penelitian dan Pengabdian kepada Masyarakat, Institut Badri Mashduqi, 2025)
This study aims to explore the implementation of flash card media in Akidah Akhlak learning for Grade II students at Cahaya Cendekia Excellent Elementary School, to identify the challenges encountered, and to assess its influence on students’ interest and understanding. The research employs a descriptive qualitative approach, with data collected through observation, interviews, and documentation, and analyzed thematically using Braun and Clarke’s Thematic Analysis model. The findings indicate that flash cards are implemented systematically and interactively, facilitating students’ understanding of abstract moral concepts, while enhancing focus, engagement, and students’ confidence to participate actively. The challenges identified include the time and effort required by teachers to prepare the media, limited printing facilities, and variations in teachers’ abilities to design visual learning media. The use of flash cards is proven to be effective in increasing learning interest and strengthening students’ understanding through a combination of visual and verbal stimulation, in line with Dual Coding theory. This study concludes that flash cards are a creative and effective learning medium that supports the internalization of moral values among elementary school students.